An analysis of Register in Champions league News Used by Goal.com - Viki Mahdiansyah; Dhanu Ario Putra; Merry Rullyanti (Literary Criticism, 2021)
This research paper aims to describe the linguistics form and the meaning of register in champion League News used by goal.com. Goal.com is a website where all about football is shared. This site is always post updated news about football, before updates, news of last match, and news of the player or the specific club. There are many new words created in football news. The type of research is descriptive qualitative. The object of this research is the register used in champions league news. The data are register words and phrases included in printed material used in goal.com. The data source is the news report of Real Madrid in Champions League. The researcher collects the news in goal.com, reads the news, and writes down the register words and phrases, and analyses the data In analyzing the data, the writer classifies the data into categories as the register, anafy7.es the data by identifying the linguistic form of the register, Identifying the differences between lexical and contextual meaning based on Larson's theory. Based on the analysis, the researcher finds that in linguistic form there are 98 data of noun, 25 data of verb, 10 data of adjective, I 04 data of compound word, 7 data of abbreviation, and 11 data of noun phrase, 7 verb phrase, and 4 adjective phrase and there are two types of meaning: 30 data of lexical meaning and 82 data of contextual meaning This means that the more frequently appear of linguistic forms are in compound word and meaning is in contextual meaning. Keyword: Sociolinguistics, Variety of Language, Register.